Cardiorespiratory fitness and cancer in women: A prospective pilot study - Baruch Vainshelboim; Ricardo M. Lima; Jonathan Myers (Elsevier, 2019)
Purpose: To assess the association between cardiorespiratory fitness (CRF) and the incidence and mortality from cancer in women, and to evaluate the potential public health implications for cancer prevention. Methods: Maximal exercise testing was performed in a pilot cohort of 184 women (59.3 ± 15.2 years) who were followed for 12.0 ± 6.9 years. Cox hazard models adjusted for established cancer risk factors and accounting for competing events were analyzed for all-type cancer incidence and mortality from cancer. Population-attributable risks and exposure impact number were determined for low CRF (<5 metabolic equivalents (METs)) as a risk factor. Results: During the follow-up, 11.4% of the participants were diagnosed with cancer and 3.2% died from cancer. CRF was inversely and independently associated with cancer outcomes. For every 1-metabolic equivalent increase in CRF, there was a 20% decrease in the risk of cancer incidence (hazard ratio (HR) = 0.80, 95% confidence interval (CI): 0.69-0.92; p = 0.001) and a 26% reduction in risk of cancer mortality (HR = 0.74, 95%CI: 0.61-0.90; p = 0.002). The population-attributable risks of low CRF were 11.6% and 14% for incidence and mortality of cancer, respectively, and the respective exposure impact numbers were 8 and 20. Conclusion: Greater CRF was independently associated with a lower risk of incidence and mortality from cancer in women. Screening for low CRF as a cancer risk factor and referring unfit individuals to a supervised exercise program could be a public health strategy for cancer prevention in middle-age women. Keywords: Exercise capacity, Exercise testing, Fitness, Public health